Death of Iraq : Stories of Life Under American Occupation, 2003-2011 - Enders, David, 1980- (Book collections on Project MUSE., 2013)
"Based on seven years of reporting by Iraqi journalist Alaa Majeed and American journalist David Enders, Death of Iraq: Stories of Life Under American Occupation, 2003-2011 traces the effects of the U.S. occupation and the ensuing civil strife through the personal narratives of seven individual citizens: a student and Iraq-born Palestinian, a Shiite imam, a farmer, a teacher, a Kurd living in the south, an oil worker and union leader, and a sheikh from Falluja leading the Awakening Movement. The stories combine powerfully to illuminate the multiple sufferings of the country and the difficulties it faces moving forward"--